O benefício infantil universal: Uma proposta de unificaç\~ao do apoio monetário à infância - Pedro Herculano Guimar\~aes Ferreira de Souza; Sergei Suarez Dillon Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This text examines the present monetary transfer setup for children aged 15 or less in Brazil. This setup is today composed of Bolsa Família's variable benefit, the Salário Família, and the child deduction in our Personal Income Tax. We analyze the value of each of the above benefits, as well as their coverage, targeting, and fiscal cost. We conclude that the present system is fragmented, is uncoordinated, excludes 1/3 of our children, and transfers higher values to wealthier children. We propose its substitution by a single Universal Child Benefit. The resources devoted to the present system could fund a R 14,62 benefit to all children under 16 in Brazil. The additional budgetary outlay for this benefit to reach R 25 - which would leave poor children no worse off than today - would be about R 6,4 billion, which amounts to about 0,2% of 2009 GDP.
Keywords: I38; 330